Secondary transmission of COVID-19 in preschool and school settings in northern Italy after their reopening in September 2020: a population-based study - Larosa, Elisabetta (Euro Surveill, 2020)
We report epidemiological investigations of transmission of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 41 classes of 36 schools in Reggio Emilia province, northern Italy, from their reopening on 1 September to 15 October 2020. The overall secondary case attack rate was 3.2%, reaching 6.6% in middle and high schools. More timely isolation and testing of classmates could be effective in reducing virus transmission in this setting.